1992
DOI: 10.1007/bf00004522
|View full text |Cite
|
Sign up to set email alerts
|

Circadian pattern of hepatosomatic index, liver glycogen and lipid content, plasma non-esterified fatty acid, glucose, T3, T4, growth hormone and cortisol concentrations in Oncorhynchus mykiss held under different photoperiod regimes and fed using demand-feeders

Abstract: The circadian patterns of several tissue and plasma metabolites, and several plasma hormone concentrations are described in rainbow trout (Oncorhynchus mykiss) that were held in groups under three different photoperiod regimes, and given free access to a demand-feeder. Regardless of photoperiod regime, all the measured parameters showed significant diel rhythms that appeared to be synchronized by dawn; dawn was represented by the concomitant onset of both light and feeding. The diel increases in hepatic glycog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 44 publications
10
45
3
Order By: Relevance
“…Several parameters assessed in controls (for instance, GK activity in liver or PK activity in hypothalamus and hindbrain) displayed clear day-night differences, which in some cases agree with those described for the same species in the literature (Boujard and Leatherland, 1992;Reddy and Leatherland, 1994;Polakof et al, 2007c;Polakof et al, 2007d), allowing us to postulate the existence of daily rhythms. Treatment with glucose during the day induced hyperglycemia, which is in agreement with similar studies carried out previously in the same fish species (Polakof et al, 2007a;CondeSieira et al, 2010a).…”
Section: Discussionsupporting
confidence: 84%
“…Several parameters assessed in controls (for instance, GK activity in liver or PK activity in hypothalamus and hindbrain) displayed clear day-night differences, which in some cases agree with those described for the same species in the literature (Boujard and Leatherland, 1992;Reddy and Leatherland, 1994;Polakof et al, 2007c;Polakof et al, 2007d), allowing us to postulate the existence of daily rhythms. Treatment with glucose during the day induced hyperglycemia, which is in agreement with similar studies carried out previously in the same fish species (Polakof et al, 2007a;CondeSieira et al, 2010a).…”
Section: Discussionsupporting
confidence: 84%
“…Those fish reared under normal housing conditions showed significant (experiment 1) or apparent (experiment 2) day-night variations of plasma cortisol with night values being higher than those measured during the day, in agreement with previous studies in the same species (Rance et al, 1982;Boujard and Leatherland, 1992) and others such as the brown trout (Pickering and Pottinger, 1983) and tilapia (Martínez-Chavez et al, 2008;Nikaido et al, 2010). Our results show that cortisol levels were higher in those acutely stressed groups (hypoxia and chasing), whereas they were lower in the high-density group in particular during the night.…”
Section: Research Articlesupporting
confidence: 91%
“…For rainbow trout, many studies have reported increased plasma cortisol at night, peaking before the light onset, then falling and remaining low during the day (Rance et al, 1982;Boujard and Leatherland, 1992). Such a daily profile is also influenced by feeding time (Boujard and Leatherland, 1992), and supports rhythmic cortisol secretion being synchronized by both photoperiod and feeding activity, with differences among seasons.…”
Section: Research Articlementioning
confidence: 92%
See 2 more Smart Citations